Spiritual harmony between the personality of the writer and his characters - Yangibayeva Nodira (Zien Journals, 2022)
There are creative people who take one or another aspect of themselves and other people to their hero, creating the basis for his experience of the "tablets of fate". Adib unwittingly absorbed his thoughts and lifestyle into the image and his actions. The character and interests of the writer are also reflected in the characters of Shukur Kholmirzayev's works. This article reveals the spiritual commonality between the writer and the characters he created
Keywords: work of art; character; writer's psychology; aesthetic function of images